Molecular Analysis of Glutinous Pigmented Rice Germplasm Through the Aid of Highly Polymorphic Markers - Caguiat, Xavier Greg; Rañeses , Mary Ann; Ticman, Henry; Chico, Martha; Arocena, Emily (International Journal For Research In Agricultural And Food Science, 2019)
The challenge for making food for less is to make it healthier and with value-added traits i.e. glutinous and pigmented. It is important in any crop breeding to increase heterosis by combining distant genotypes and this could be achieved through the use of molecular markers. This study aimed to assess the genetic distance of 83 entries with 71 elite lines consisted of pigmented, glutinous and pigmented- glutinous rice, 9 parent lines and one check variety, NSIC Rc19. Preliminary survey of 300 genome-wide microsatellite markers led to 17 highly polymorphic markers. Overall diversity among the entries is 48% which is expected among sister lines. A 100% similarity was observed for two pairs of elite lines. Dendrogram generated based on UPGMA formed two major clusters with one elite line Line21 and Traditional4 and Traditional7 in one cluster while the rest of the entries formed the other cluster. Without markers, the breeding of special purpose rice including combination of pigmented and glutinous rice varieties would take longer but with highly polymorphic microsatellite markers could accelerate the development of new special purpose rice varieties.